Dietary intake, nutritional adequacy and food sources of vitamins involved in the methionine-methylation cycle from Spanish children aged one to <10 years: results from the EsNuPI study - Partearroyo, Teresa; Samaniego-Vaesken, María de Lourdes; Rodríguez-Alonso, Paula; Soto-Méndez, María José; Hernández-Ruiz, Ángela; Gil, Ángel; Varela-Moreiras, Gregorio (Frontiers in Nutrition, 2023)
Methionine-methylation cycle and the derived critical functions during infancy are key regulated by folates, vitamins B12, and B6. Objective was to evaluate folates intakes alongside with vitamins B6 and B12 while describing their major dietary contributors in Spanish children aged one to <10 years. A total of 1,448 children between the ages of 1 to <10 years (49.7% girls and 50.3% boys) from the EsNuPI study were allocated into two cohorts: one Spanish Reference Cohort (SRS) of the general population, and another including children consuming adapted milks called Adapted Milk Consumers Cohort (AMS). The median intake of vitamin B6 was 1.35 (1.06 – 1.70) mg/day in the SRS and 1.45 (1.17 – 1.79) mg/day in the AMS, being significantly higher in the AMS for all age-groups. Prevalence of adequacy for vitamin B6 in the SRS and AMS was 97.7% and 98.7%, respectively. Total folates intakes in the AMS were significantly higher (p≤ 0.001) in all age groups than in the SRS, independently of age. In addition, the prevalence of adequacy for folates intakes in all groups was more than 60%. Vitamin B12 intake increased with age independently of the type of milk consumed. The prevalence of adequacy for vitamin B12 was highly compliant by all population groups. The major contributors to vitamin B6 were milk and dairy products being significantly higher in AMS than SRS (p≤0.001). The highest contributors to folates intakes were milk and dairy products, cereals, vegetables, and fruits in both groups whereas for vitamin B12 in the SRS sample were milk and dairy products followed by meat and meats products and for adapted milks, were milk and dairy products, followed by eggs, then meat and meats products. A satisfactory prevalence of adequacy for vitamins B6, and B12 amongst the Spanish children population was observed, which was not the case for folates, regardless of the dietary group evaluated. Nevertheless, a possible strategy to increase folate intake among the youngest children is to increase the consumption of milk and dairy products within a healthier dietary pattern, as these may contribute significantly to the vitamin needs of the infant population.